Association between thyroid cysts and hypertension by atherosclerosis status: a cross-sectional study - Yuji Shimizu (Nature Portfolio, 2021)
Abstract Our recent studies indicate that thyroid cysts have clinical implications. Thyroid cysts could have a positive effect on the supply of thyroid hormones. Both hyperthyroidism and hypothyroidism cause hypertension. Hypothyroidism, but not hyperthyroidism, is a risk factor for atherosclerosis. Therefore, thyroid cysts could be associated with hypertension, and atherosclerosis might influence the association between thyroid cysts and hypertension. To evaluate the clinical significance of thyroid cysts, a cross-sectional study was conducted with 1801 Japanese aged 40–74 years. Thyroid cysts were significantly positively associated with hypertension in participants without atherosclerosis. However, there was a significant inverse association in those with atherosclerosis. The potential confounding factor adjusted odd ratios and 95% confidence intervals (95% CIs) were 1.49 (95% CI 1.17–1.90) for participants without atherosclerosis and 0.49 (95% CI 0.24–0.98) for those with atherosclerosis. The present study demonstrates that thyroid cysts have clinical implications because thyroid cysts support thyroid hormone activity. Our findings provide sufficient evidence to develop a risk assessment for hypertension for the general population, even though further research is required.